Duodenal–jejunal bypass improves diabetes and liver steatosis via enhanced glucagon‐like peptide‐1 elicited by bile acids. Issue 2 (February 2015) - Kashihara, Hideya; Shimada, Mitsuo; Kurita, Nobuhiro; Sato, Hirohiko; Yoshikawa, Kozo; Higashijima, Jun; Chikakiyo, Motoya; Nishi, Masaaki; Takasu, Chie
Abstract Background and Aim Bariatric surgery not only elicits weight loss but also rapidly resolves diabetes. However, the mechanisms remain unclear. The present study investigates how diabetes and liver steatosis are improved after duodenal–jejunal bypass (DJB) compared with a glucagon‐like peptide‐1 (GLP‐1) analog and correlations between bile acids and GLP‐1 secretion. Methods We initially determined the effects of bile acids on GLP‐1 in vitro and then assigned 12 male 16‐week‐old Otsuka Long‐Evans Tokushima Fatty rats to groups that underwent DJB, a sham operation, or were treated with the GLP‐1 receptor agonist, liraglutide (n = 4 each). Blood glucose, insulin, GLP‐1, serum bile acids, liver steatosis, and the number of GLP‐1 positive cells (L cells) in the small intestine and colon were investigated in the three groups at eight weeks postoperatively. Results Levels of GLP‐1mRNA were upregulated and GLP‐1 secretion increased in cells incubated with bile acids in vitro. Weight gain was suppressed more in the DJB than in the sham group in vivo. Diabetes was more improved and GLP‐1 levels were significantly higher in the DJB than in the sham group. Serum bile acids were significantly increased, the number of L cells in the ileum was upregulated compared with the sham group, and liver steatosis was significantly improved in the DJB compared with the other two groups. Conclusions Duodenal–jejunal bypass might improve diabetes and liver steatosis by enhancing GLP‐1 secretion through increasing serum bile acids and the proliferation of L cells in the ileum, compared with liraglutide.